KARAKTERISTIK PERUBAHAN FUNGSI RUANG RUMAH SEDERHANA BERSUBSIDI (STUDI KASUS : PERMUKIMAN BSS 2- MONCONGLOE) - Marwati Marwati (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2021)
Abstract: The need for housing is an essential thing in the development of human life, including the provision of accommodation for the lower middle class with subsidized housing. Simultaneous and large number of subsidized housing developments occur in the buffer areas of Makassar City, one of which is Moncongloe District. Changes and additions to the core house occurred in less than five years since it was built. Control of additional space requires supervision from the aspect of the function and health of the occupants. This study aims to determine the characteristics of changes in position and spatial patterns in the post-occupancy period. The study location is in the Bumi Salam Sejahtera (BSS) 2 housing complex in Moncongloe District using a purposively selected sample of houses that have undergone changes. The data from the observations were then analyzed descriptively by comparing with the floor plan of the main house. The results of the study found that changes in location occurred in the bathroom space and the addition of sleeping space, business and drying. Occupants need to pay attention to the factors of good lighting and air circulation in the post-change or addition of space to the house.